2022
DOI: 10.1002/pmic.202200074
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitinomics: History, methods, and applications in basic research and drug discovery

Abstract: The ubiquitin‐proteasome system (UPS) was discovered about 40 years ago and is known to regulate a multitude of cellular processes including protein homeostasis. Ubiquitylated proteins are recognized by downstream effectors, resulting in alterations of protein abundance, activity, or localization. Not surprisingly, the ubiquitylation machinery is dysregulated in numerous diseases, including cancers and neurodegeneration. Mass spectrometry (MS)‐based proteomics has emerged as a transformative technology for cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 154 publications
0
15
0
Order By: Relevance
“…While some direct evidence of N-terminal ubiquitylation was obtained in these early studies by mass spectrometry ( Ben-Saadon et al, 2004 ; Coulombe et al, 2004 ), until recently no quantitative proteomics data was available on this modification. The global profiling of isopeptide-linked ubiquitylation sites was revolutionized a decade ago by the development of an antibody recognizing the diglycine remnant present on ubiquitylated lysines after tryptic digestion ( Xu et al, 2010 ), fast becoming the method of choice for enrichment and identification of ubiquitylated sites ( Kim et al, 2011 ; Udeshi et al, 2013 ; Steger et al, 2022 ). A major drawback of this technique however is that, due to the nature of the antibody epitope, it does not enrich for peptides originating from N-terminally ubiquitylated proteins.…”
Section: N-terminal Ubiquitylationmentioning
confidence: 99%
See 1 more Smart Citation
“…While some direct evidence of N-terminal ubiquitylation was obtained in these early studies by mass spectrometry ( Ben-Saadon et al, 2004 ; Coulombe et al, 2004 ), until recently no quantitative proteomics data was available on this modification. The global profiling of isopeptide-linked ubiquitylation sites was revolutionized a decade ago by the development of an antibody recognizing the diglycine remnant present on ubiquitylated lysines after tryptic digestion ( Xu et al, 2010 ), fast becoming the method of choice for enrichment and identification of ubiquitylated sites ( Kim et al, 2011 ; Udeshi et al, 2013 ; Steger et al, 2022 ). A major drawback of this technique however is that, due to the nature of the antibody epitope, it does not enrich for peptides originating from N-terminally ubiquitylated proteins.…”
Section: N-terminal Ubiquitylationmentioning
confidence: 99%
“…Mass spectrometry is usually considered the gold standard to identify protein ubiquitylation sites ( Steger et al, 2022 ) but unless machines are specifically programmed to search for non-lysine ubiquitylation this information is simply lost amongst the thousands of unassigned spectra ( Pathan et al, 2017 ). Ubiquitin proteomics is typically accompanied by an enrichment step, often involving purification using a linkage-specific ubiquitin binder ( Hjerpe et al, 2009 ; Emmerich et al, 2013 ; Michel et al, 2017 ; Antico et al, 2021 ) or peptide enrichment using an antibody recognizing the diGly remnant attached to ubiquitylated lysines following tryptic digest ( Xu et al, 2010 ).…”
Section: Experimental Approaches To Probe Non-canonical Ubiquitylatio...mentioning
confidence: 99%
“…One could also consider omitting sample alkylation since this will avoid di-carbamidomethylation of lysines (and other amino acid residues) while still obtaining relatively high PSM match rates Include appropriate negative affinity-enrichment controls to determine the true false discovery rate of the K-ε-GG footprint (or K + 114) and that affinity enrichment for-K-ε-GG containing peptides is highly selective. Use parallel alternative methods to enrich for peptides with ubiquitination; there are several independent methods now available. ,,, Perform an open search on the acquired MS data to ensure that the mass modifications in the data are consistent with the intended sample handling. For the analysis of MS data, include only the most relevant (variable) modifications (ideally based on open searches) and site scoring algorithms to reduce false discovery rate of ubiquitination (in particular +57.022 and +114.0429 Da on lysine, cysteine, and peptide N terminus). The sequence database used for MS data analysis should include all proteins of the target organism (e.g., Arabidopsis predicted protein sequences in Araport11 or TAIR10) as well as additional proteins that may be in the sample (including contaminants such as keratin, trypsin, and E. coli proteins) not just proteins of interest. …”
Section: Discussionmentioning
confidence: 99%
“…60,61 The determination of the nature of the substrate ubiquitination is technically challenging. 36,37,61 Figure 2D of Sun et al 1 showed a linkage analysis indicating that 32% was from ubiquitin K48 (no further information was provided on this analysis). It was stated that "because K48 was the most abundant linkage type, much of the chloroplast ubiquitinome can be assumed to be primed for proteasomal degradation."…”
Section: Journal Ofmentioning
confidence: 97%
See 1 more Smart Citation